Hypoxia-based strategies for regenerative dentistry—Views from the different dental fields. (September 2017) - Müller, Anna Sonja; Janjić, Klara; Lilaj, Bledar; Edelmayer, Michael; Agis, Hermann
Highlights: Hypoxia signaling and "cellular oxygen sensors" play a key role in tissue regeneration. The increase in the number of studies on hypoxia signaling and hypoxia based strategies highlights the importance for regenerative dentistry. Here the role of hypoxia signaling and an overview of hypoxia-based strategies for regenerative approaches in dental specialties are presented. Abstract: The understanding of the cell biological processes underlying development and regeneration of oral tissues leads to novel regenerative approaches. Over the past years, knowledge on key roles of the hypoxia-based response has become more profound. Based on these findings, novel regenerative approaches for dentistry are emerging, which target cellular oxygen sensors. These approaches include hypoxia pre-conditioning and pharmacologically simulated hypoxia. The increase in studies on hypoxia and hypoxia-based strategies in regenerative dentistry highlights the growing attention to hypoxia's role in regeneration and its underlying biology, as well as its application in a therapeutic setting. In this narrative review, we present the current knowledge on the role of hypoxia in oral tissues and review the proposed hypoxia-based approaches in different fields of dentistry, including endodontics, orthodontics, periodontics, and oral surgery.